PERAN STAKEHOLDER DALAM PEMBANGUNAN PARIWISATA DI PULAU SAMOSIR - Simanjorang, Feronica; Hakim, Luchman; Sunarti, Sunarti (FIA UB, 2020)
Samosir Island is known as the tourism center of Lake Toba Region that is managed based on DMO concept in 2010-2015. This study aims to identify the profile and tourism attractivenessÂ of Samosir Island, and toidentify and analyze the role of stakeholders through DMO. The researcher used descriptive methods, and used primary and secondary data collected by observation, interview and documentation techniques. The results showed that most of the tourism activities on Samosir Island are related to Batak culture so that local community has an important role in maintaining the sustainability of attractions. There has not been found any good cooperation relations between the government, local communities, and the private sector in the development of Samosir Island tourism. Local communities choose to manage resources especially cultural sites independently. Similar conditions are also found in the private sector where business activities have not been running wuth an appropriate management strategy. Lack of continous control by the local government causes a decrease in the quality of service providers related attractions, amenities, and accessibility.